Hermenêutica e dialética no direito - Danilo Ribeiro Peixoto (2014)
This dissertation registers the development of a research that intended to critically examine interpretation and enforcement of Law from a rationality both dialectical and able to apprehend the juridical phenomenon according to ontological Hermeneutics. Presupposing that Law has to be comprehended dynamically and systematically leads us to recognize the limitations of comprehending Law from purely formal and Cartesian premises. Hegelian Dialectics, which ruptured with formalism and achieved reconciliation of the many divisions that reason has suffered in the past, was taken as the theoretical mark. Hegelian Dialectics is revealed as the logic of object and has as its main elements contradiction, movement and totality. It also achieves as result the unveiling of the truth of concept and do not restricts itself only by achieving a formal validity of logical reasoning. Hans-Georg Gadamers Philosophical Hermeneutics, adopted in this work, takes Hegelian Dialectics as one of its most important theoretical references. Besides Hegelian Dialectics, Gadamer retakes Platonic-Socratic Dialectics and develops his own dialectical conception. Universalization of hermeneutical phenomenon and the refutation of methodical ideal as a guarantee of achieving truth could be highlighted among distinguished merits that Gadamerian theory possesses. Law enforcement presupposes the way of understanding Law and thus is directly related to a concept of Law. Juridical reasoning reveals itself strongly affected by the concept of Law formulated by Legal Positivism, which is supported on excessively formalist premises of reasoning. If a way of understanding Law according to a dialectical reasoning and guided by ontological Hermeneutics is looked for, then this kind of formalist reasoning must be opposed. R. Dworkins and F.Müllers thought was taken as reference for a critical and hermeneutically conscious treatment of the concept of Law. This work encountered on Dialectics an important reference that enables to guide juridical thought through a total comprehensive understanding of Law. Judges are more than simple juridical operators, they appear as some kind of qualified hermeneuticists that act constitutively on creation and concretion of Law, as well as on the realization of justice.